Breathing within the history (1900–2016): The ever-evolving 'making' in the art studio at Teachers College. Issue 2 (1st June 2016) - Koo, Sohee
Purposes for studio art and manual training courses taught in the early 1900s have been widely debated. Many scholars, such as Bonser and Efland, have discussed the importance of industrial arts from a social and cultural context, which has an interesting parallel to the contemporary maker movement and the use of digital fabrication in education. In recent times, the fast-growing significance of technology in the classroom has been debated broadly. Resnick (2006) and Blikstein (2013), for example, argue that 'making' by using digital fabrication could be a vehicle for inspiring innovative ideas and literacies. Yet we know very little about how studio art courses have evolved over time. Clay modelling, weaving and woodworking classes existed during the early 1900s under the direction of Arthur Wesley Dow's (1857–1922) chairmanship in the Fine Arts Department at Teachers College. Using Dow's time at Teachers College as a starting point for consideration, how did studio art classes at this institution shift over time? Moreover, what is the focus of studio art classes at Teachers College when considering the current emphasis directed towards technology integration? This article examines studio art and art education influenced by Dow's philosophy of manual arts training during the 1900s in order to better understand and synthesize today's notion of 'making' in contemporary fabrication studios and studio art courses. Using a historical research methodology, Dow's philosophy of art education and studio courses are analysed by examining primary sources such as Dow's lecture notes. Such exploration may suggest innovative ideas and directions for integrating new technologies in today's studio art courses within the field of art education.